Mycobacterium Tuberculosis Identification on Suspected Extra Pulmonary Tuberculosis Patients - Lipinwati, Lipinwati; Hanina, Hanina; Wulandari, Putri Sari; Iskandar, Mirna Marhami; Istarini, Attiya; Miranda, Melly; Dewi, Hasna; Juniati, Rianita; Fairuz, Fairuz (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Extra Pulmonary Tuberculosis (EPTB) is Tuberculosis infection in organs other than the lungs, like pleura, lymph nodes, abdomen, genitourinary tract, skin, joints and bones, or meninges. The Diagnosis of EPTB is still challenging because symptoms of EPTB is vary, location EPTB is an inaccessible site, and paucibacillary smear. We wanted to know the Mycobacterium tuberculosis identification using the qPCR method on samples of EPTB suspects. Methods: This research was a descriptive research with laboratory experiments. Subjects in this study were all cases of suspected EPTB with clinically diagnosed, thoraks radiographs, colonoscopy, and formalin fixed paraffin embedded (FFPE). DNA extraction was carried out according to  PureLink® Genomic dna extraction kit instructions. The PCR volume 20 ul with 2x QuantiNova SYBR Green PCR Kit, M.tuberculosis Primer IS 6110, and DNA Sample. QPCR temperatures was done with predenaturation at 95 °C for 3 minutes, and followed 45 cycles, consist of denaturation at 95 °C for 15 seconds, annealing at 60 °C for 30 seconds dan extenstion at 72 °C for 30 seconds. PCR was performed with positive and negative controls, and data analysis was based on positive and negative ct controls. Results: From 30 suspect EPTB samples, there are males (56,67%), with age 36-55 yo (50%), site of samples most from gastrointestines (70%), and there are 6 samples (20%) with positive qPCR. Conclusion: qPCR methods can be used for EPTB diagnosis.